Analysis of liquid metal foams through X-ray radioscopy and microgravity experiments - HUTZLER, STEFAN (My University, 2014)
Complex liquid structures such as metallic foams were produced in a furnace that allowed in situ X-ray monitoring of the evolution of the structure and distribution of the liquid in the foam. The experiments were carried out during parabolic flights which provided varying levels of gravity. The evolution of the characteristic liquid fraction profiles due to gravity induced drainage was measured and analysed in terms of the foam drainage equation, obtaining viscosity and surface tension by fitting solutions of the equation to the experimental data. The surface tension of the melt in the foam was decreased up to 40%. Effective viscosities of up to 139 times the viscosity of a pure bulk melt were observed. These effects could be attributed to the smaller influence of solid particles dispersed in the melt and the larger influence of the complex foam structure.
PUBLISHED
Keywords: metallic foams; metallic foams; Nanoscience & Materials; MATERIALS SCIENCE; Physics